Treatment strategies for extremity sarcoma patients: a population-based analysis on German clinical cancer registry data - Müller, Jörg Andreas; Delank, Karl-Stefan; Laudner, Kevin; von Rüsten, Anne; Schneider, Constanze; Selig, Jessica Isabel; Wittenberg, Ian; Zeh, Alexander; Vordermark, Dirk; Medenwald, Daniel (Frontiers in Oncology, 2025)
BackgroundSarcomas represent a heterogenous group of neoplasms, and there is a lack of data describing treatment patterns in Germany. The specific aim of this study was to evaluate treatment strategies and therapeutic outcomes of extremity sarcoma based on German cancer registry data.MethodsFrom 2000 to 2023, we identified n=3,094 patients diagnosed with extremity sarcoma from the German clinical cancer registries of Brandenburg-Berlin, Saxony and Saxony-Anhalt. Using logistic regression and Cox-proportional hazard analysis, we determined predictors of overall survival (OS). Propensity-score matching (PSM) was used to balance covariates and to reduce potential bias. We included sex, age at diagnosis, tumor localization, histological grade, Eastern Cooperative Oncology Group (ECOG) performance status, T-status and treatment as parameters in our regression models. To assess the robustness of our findings in the presence of missing data, we conducted a sensitivity analysis using multiple imputation.ResultsA total of 2,240 propensity score-matched patients with extremity sarcomas were included. In multivariable Cox regression, higher age, high tumor grade, and advanced T-status were significantly associated with increased mortality. Treatment with radiotherapy (RT) alone was linked to worse survival (HR 1.82, 95% CI 1.12–2.95, p = 0.015), whereas neoadjuvant RT and surgery alone showed no survival advantage compared to adjuvant RT. The median OS was longest for patients treated with surgery alone (194 months) and adjuvant RT (146 months), and shortest with RT alone (82 months). Sensitivity analyses using multiple imputation confirmed the robustness of the results.ConclusionsAdjuvant RT and surgery alone were associated with the most favorable survival outcomes in patients with extremity sarcomas. Advanced age, tumor grade, and T-stage were strong negative prognostic factors. RT without surgery was linked to significantly reduced survival.